1993
DOI: 10.2307/1534097
|View full text |Cite
|
Sign up to set email alerts
|

Le suicide en milieu carceral

Abstract: Bourgoin (Nicolas).-Le suicide en milieu carcéral Le suicide en prison attire particulièrement l'attention des spécialistes depuis la crise de sursuicidité carcérale qui prend naissance en 1972. L'objet de cet article est d'évaluer dans quelle mesure les gens se suicident plus en prison qu'en liberté, d'établir des comparaisons entre suicide carcéral et suicide en milieu libre selon le mode et le profil socio-démographique du suicidé sur un nombre élevé de cas, et d'essayer de mesurer le lien entre le suicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Studies that faced the issue of suicide in prison have indirectly confirmed the presence of a higher suicide rate among prisoners for homicide than other inmates [ 4 , 39 , 40 , 41 ]. The suicide-risk data among the prisoners convicted revealed that risk is higher when inmates are alone in their cells, e.g., [ 42 ], or located in a disciplinary cell, e.g., [ 43 ]. In addition, those convicted for violent and sexual crime behavior, e.g., [ 44 ], and those serving long sentences, e.g., [ 45 ], present generally a much higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that faced the issue of suicide in prison have indirectly confirmed the presence of a higher suicide rate among prisoners for homicide than other inmates [ 4 , 39 , 40 , 41 ]. The suicide-risk data among the prisoners convicted revealed that risk is higher when inmates are alone in their cells, e.g., [ 42 ], or located in a disciplinary cell, e.g., [ 43 ]. In addition, those convicted for violent and sexual crime behavior, e.g., [ 44 ], and those serving long sentences, e.g., [ 45 ], present generally a much higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the proportion of suicides which during DSC range from 8% to 17% in France (Bourgoin, 1993b;Duthé et al, 2013Duthé et al, , 2014Hazard, 2008;Vanhaesebrouck et al, 2022) and from 3% to 54% in studies located in other countries (Kovasznay et al, 2004;Reeves & Tamburello, 2014;Spinellis & Themeli, 1997). The risk of suicide was found to be much higher during DSC (20 times higher), in line with previous studies (Bourgoin, 1993b;Duthé et al, 2013Duthé et al, , 2014Reeves & Tamburello, 2014). In France, it has not decreased since the period 2006-2009 (16 times higher) (Duthé et al, 2013), despite the fact that the fight against suicide during DSC is one of the five main axes of a national plan for the prevention of suicide in prison initiated in 2009 (La Garde des Sceaux, 2009).…”
Section: Disciplinary Solitary Confinementmentioning
confidence: 99%
“…Importantly, these events have only received little attention from comparative studies, which mainly focused on factors stable over time (Zhong et al, 2021). To our knowledge, only three studies assessed the relationship between DSC and suicide (Bourgoin, 1993b;Duthé et al, 2014;Reeves & Tamburello, 2014). They all found a suicide risk more than 10 times higher than the one associated with conventional detention.…”
Section: Introductionmentioning
confidence: 99%
“…This piece of research resulted in a set of administrative guidelines based on risk factors that drew on a ‘rational choice’ theory of suicide (see Table 1). As Bourgoin (1993: 622) states: ‘A significant proportion of suicides is due to deception resulting from denial to an inmate’s demand or from failed escapes.’ In accordance with neo-classical economic theory, Bourgoin breaks down the number of recorded suicides by place (i.e. areas within prisons) and date, to enable prison staff to identify potentially suicidal prisoners.…”
Section: The Development Of Specific Actuarial Risk Management and Dementioning
confidence: 99%
“…areas within prisons) and date, to enable prison staff to identify potentially suicidal prisoners. Bourgoin (1993: 609–610) explains the higher suicide rates in prison compared to those in society as a product of the oppressive effect of incarceration. Suicide, in short, is caused by the prison (Bourgoin, 1993: 622).…”
Section: The Development Of Specific Actuarial Risk Management and Dementioning
confidence: 99%